(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
With the increasing usage of ICT in the field of Ecommerce, more and more retailers have registered their presence in the online retail business. All the online stores are offering variety of products and services to customers and thus, it has become tough to capture a larger share of market for any online store. Therefore, nowadays satisfaction of customers has become a major aspect which will help e-retailers to increase their sales and profits by increasing the customer base. This study aims to measure the satisfaction level of customers in online shopping and the major factors which influence their satisfaction. The design of present study is descriptive and analytical. Primary data has been collected with the help of a structured questionnaire from 180 respondents. Result of factor analysis identified six major factors which influence online customers’ satisfaction which are as follows Security and Privacy, Website Design, Information Quality, Customer Service, Price and Quality of the product, Availability and Fulfillment. The findings of the study also revealed that majority of the customers are moderately satisfied from online shopping.